DNA damage in oocytes induces a switch of the quality control factor TAp63α from dimer to tetramer. - Deutsch, G; Zielonka, E; Coutandin, D; Weber, T; Schäfer, B; Hannewald, J; Luh, L; Durst, F; Ibrahim, M; Hoffmann, J; Niesen, F; Sentürk, A; et al. (2011)
TAp63α, a homolog of the p53 tumor suppressor, is a quality control factor in the female germline. Remarkably, already undamaged oocytes express high levels of the protein, suggesting that TAp63α's activity is under tight control of an inhibitory mechanism. Biochemical studies have proposed that inhibition requires the C-terminal transactivation inhibitory domain. However, the structural mechanism of TAp63α inhibition remains unknown. Here, we show that TAp63α is kept in an inactive dimeric state. We reveal that relief of inhibition leads to tetramer formation with ∼20-fold higher DNA affinity. In vivo, phosphorylation-triggered tetramerization of TAp63α is not reversible by dephosphorylation. Furthermore, we show that a helix in the oligomerization domain of p63 is crucial for tetramer stabilization and competes with the transactivation domain for the same binding site. Our results demonstrate how TAp63α is inhibited by complex domain-domain interactions that provide the basis for regulating quality control in oocytes.